2018
DOI: 10.3791/57017
|View full text |Cite
|
Sign up to set email alerts
|

Engineering 'Golden' Fluorescence by Selective Pressure Incorporation of Non-canonical Amino Acids and Protein Analysis by Mass Spectrometry and Fluorescence

Abstract: Fluorescent proteins are fundamental tools for the life sciences, in particular for fluorescence microscopy of living cells. While wild-type and engineered variants of the green fluorescent protein from Aequorea victoria (avGFP) as well as homologs from other species already cover large parts of the optical spectrum, a spectral gap remains in the near-infrared region, for which avGFP-based fluorophores are not available. Red-shifted fluorescent protein (FP) variants would substantially expand the toolkit for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…This approach is based on the substrate tolerance of cellular systems [ 81 ]. Endogenous aaRS play a crucial role in replacing the cAAs in protein with one or more amino acid analogs that have similar structures to those of the cAAs [ 82 ]. The auxotrophic hosts are cultured in a medium that initially contains a limited amount of nAAs.…”
Section: Methods For Ncaas Incorporation Into Proteinsmentioning
confidence: 99%
“…This approach is based on the substrate tolerance of cellular systems [ 81 ]. Endogenous aaRS play a crucial role in replacing the cAAs in protein with one or more amino acid analogs that have similar structures to those of the cAAs [ 82 ]. The auxotrophic hosts are cultured in a medium that initially contains a limited amount of nAAs.…”
Section: Methods For Ncaas Incorporation Into Proteinsmentioning
confidence: 99%
“…For example, when the pH is increased from 3 to 7, the λ em of 4NH 2 -Trp-containing barstar is decreased from 358 to 338 nm, whereas the λ ab of the 5NH 2 -Trp variant exhibits shifts from 363 to 375 nm when the solution pH is increased from 7 to 9. In addition, Budisa and co-workers have demonstrated that aminotryptophans could be used to change the color of green fluorescence protein (GFP) as well as other protein systems. …”
Section: Fluorescence Probesmentioning
confidence: 99%
“…This provides suitable bio-orthogonal reactive groups (‘handles’) amenable for various chemoselective ligand couplings. In addition, both site- and residue-specific incorporation techniques generally allow for fine chemical manipulations of the amino acid side chains, e.g., of Pro, Trp, Tyr, Met and to visualize them in spectroscopic recordings ( Baumann et al, 2018 ).…”
Section: Recombinant Lanthipeptides Produced By Incorporating Non-canmentioning
confidence: 99%